Analisis Arus Bocor Pada Instalasi Listrik Dengan Sistem Proteksi Residual Current Breaker With Overcurrent Protection 6 Ampere 1 Fasa - Nurhabibah Naibaho; Pebrianto Silitonga (JURNAL ELEKTRO, 2025)
This study is an option for the safety system of residential electrical installations from the danger of electrical disturbances such as overloads, short circuits and electric shocks that can endanger our safety. Residual Current Breaker with Overcurrent Protection is a combined component of the MCB and ELCB that stops the flow of electricity when an overload, short circuit, or leakage current occurs. Therefore, the author presents the function of RCBO in this study and the research flow is also explained in this study. The In magnitude of the RCBO installed was In = 6 Ampere in this study with high sensitivity (30 mA). After RCBO testing is carried out on the overload used with In 6 Ampere with high sensitivity of 30 mA, the RCBO will be tested with a load current of 9.04 Ampere, then the RCBO will be trif. At the time of a short connection with a load power of about 800 Watts the RCBO trives, and an electric shock with a load of about 800 Watts the RCBO trif, and an electric shock with a load of about 800 Watts RCBO experienced a trif. To determine the rating magnitude of RCBO current (In), from the results of the current calculation at the load, which is 5.34 Ampere, RCBO with In = 6 Ampere is chosen because there is no RCBO that has a nominal current value of 5 Ampere.